2022
DOI: 10.1108/par-01-2022-0014
|View full text |Cite
|
Sign up to set email alerts
|

Do board secretaries influence annual report readability?

Abstract: Purpose The purpose of this study is to investigate the impact of board secretaries’ characteristics on annual report readability using an original method that evaluates the readability of Chinese characters. Design/methodology/approach The authors manually collect board secretaries’ characteristics from the China Securities Market and Accounting Research database and obtain annual reports from the China Information website. Ordinary least square regression is applied to evaluate the impact, and then robustn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 65 publications
10
8
0
Order By: Relevance
“…The findings indicated that the age of directors had significantly eased the readability of financial reports. The findings by Xu et al (2018) agreed with the findings of Sun et al (2022) in China but disagreed with the findings of Efretuei (2013) in the UK who found that older directors were associated with more difficult-to-read financial statements.…”
Section: Empirical Literature Reviewsupporting
confidence: 49%
See 3 more Smart Citations
“…The findings indicated that the age of directors had significantly eased the readability of financial reports. The findings by Xu et al (2018) agreed with the findings of Sun et al (2022) in China but disagreed with the findings of Efretuei (2013) in the UK who found that older directors were associated with more difficult-to-read financial statements.…”
Section: Empirical Literature Reviewsupporting
confidence: 49%
“…The descriptive statistics findings in Table 2 indicate that the average Flesch readability ease score in Kenyan listed firms was 15.77% which implies that the financial statements of Kenyan listed companies are very difficult to read which was comparable to the Ginesti and Drago (2018) in Italy which found that financial statements are hard to read using the Fog measure of 15.1%. As per the descriptive statistics findings in Table 2, female directors constituted 31.1% of board members which was higher than the female directorship proportion in Italy which stood at 7% (Ginesti and Drago, 2018) and 23.2% in China (Sun et al, 2022). The average age of directors in Kenyan listed firms is 59 years as per Table 2 which is comparable with other countries such as the USA which is 53 years (Xu et al, 2018) and 54 years in the UK (Efretuei, 2013).…”
Section: Findings On Descriptive Statisticsmentioning
confidence: 77%
See 2 more Smart Citations
“…Although strategic emphases through these three channels are central to the level of readability in an annual report, there remains a possibility that managerial ability is another critical factor affecting this relationship. Sun et al’s (2022b) finding that board secretaries’ legal-professional expertise, international expertise and role duality improve annual report readability supports this idea. Firms with SE on VA over VC lead to better current profitability, and more experienced managers will state their superior performance with clear and transparent words that reveal the superior performance without exhausting explanations, highlight significant financial success by facilitating an information-rich environment and attribute success to “managers’ foresight” Conversely, firms with SE on VC over VA suffer from poor earnings in the short-term period, and more skilled managers will hide their poor performance with vague words that confuse both stakeholders and competitors, buy time to recover from the initial R&D spending and shield them from blame regarding market failures.…”
Section: Introductionmentioning
confidence: 92%